Synthesis and structural features of 5-(4-(tert-butyl) phenyl)-4-((R)amino)-4H-1,2,4-triazole-3-thiols - I. I. Aksyonova-Seliuk; O. I. Panasenko; E. G. Knysh (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Chemistry of heterocyclic compounds is one of the most popular sector in organic chemistry. Scientists allocate among them a class of derivatives of 1,2,4-triazole. This class of compounds attracts attention his broad spectrum of biological activity. There are antiviral, anti-inflammatory, anti-tubercular, antimicrobial, antioxidant, actoprotective, anti-cancer and other activities. The derivatives of 1,2,4-triazole have one more important advantage. It is low toxicity. This properties do this class of derivatives promising for researches their chemical structure and biological activity and purposeful search of biologically active substances. The purpose of the work is synthesis of 5-(4-(tert-butyl)phenyl)-4-((R)amino)-4H-1,2,4-triazoles-3-thiols from appropriate ylidene derivatives of 4-amino-5-(4 (tert-butyl)phenyl)-4H-1,2,4-triazoles-3-thiol and research of their physical and chemical properties. The objects of research were 10 new compounds, derivatives of 4-amino-5-(4-(tert-butyl)phenyl)-4H-1,2,4-triazoles-3-thiol. These compounds are the crystal substances which are odorless, insoluble in water and soluble in organic solvents. Investigation of the physical and chemical properties of this compounds was carried out according to the methods listed in the State Pharmacopoeia of Ukraine. The melting temperature of synthesized compounds was determined by device OptiMelt Stanford Research Systems MPA100. The structure of the compound was confirmed by 1H-NMR spectroscopy (Mercury 400) and gas chromatography-mass spectrometry (Agilent 1260 Infinity HPLC). 10 new compounds, derivatives of 4-amino-5-(4-(tert-butyl)phenyl)-4H-1,2,4-triazoles-3-thiol, were synthesized in a study. The chemical structure of the new compounds was confirmed by modern instrumental methods of analysis. Results of the done work can be use in the future search of biologically active substances.